(untitled) (LEARNing Landscapes, 2010)
In this commentary, business man and philanthropist Avrum Morrow maintains that learning need not be dull. He recalls some of the passionate teachers, from primary school to university, who had a profound influence on him. Through innovative art projects and singing arias in class to attention-grabbing science demonstrations, these teachers sparked his interest in art, music and science. He believes that curiosity and a receptive mind are the keys to lifelong learning.